Doctor‐to‐doctor communication of prognosis in metastatic cancer: a review of letters from medical oncologists to referring doctors. Issue 9 (September 2015) - Moth, E. B; Parry, J.; Stockler, M. R; Beale, P.; Blinman, P.; Della‐Fiorentina, S.; Kiely, B. E
Abstract Background Shared understanding of prognosis is vital for optimal, multidisciplinary, clinical decision making. Aims This study aims to determine the frequency and nature of prognostic information in medical oncologists' letters to referring doctors for patients with metastatic cancer. Methods We reviewed all consultation letters (to June 2014) for new patients with metastatic cancer presenting to medical oncologists at Concord and Macarthur Cancer Centres between June 2012 and June 2013. We recorded the presence and nature of prognostic information in the letters, patients' characteristics and survival. Characteristics associated with inclusion of prognostic information were explored. Results We analysed 1344 letters pertaining to 272 patients with a median survival of 13 months. The median number of letters per patient was 4 (interquartile range 1–7), with 50% written by trainees. The terms 'metastatic' or 'stage IV cancer' were included in letters for 253 patients (93%), treatment was described as 'palliative' for 174 patients (64%) and the word 'incurable' was included for 93 (34%). Only 31 patients (11%) had a quantitative estimate of prognosis in any correspondence: median or average survival in 14, general time frame in 12 and, best case, typical and worst case scenarios in 5. Inclusion of quantitative prognostic information was not associated with patient age, cancer type, treatment plan, trainee authoring letter or shorter survival. Conclusion Inclusion of quantitative prognostic information in written correspondence from medical oncologists regarding patients with metastatic cancer was infrequent. Encouraging oncologists to include quantitative prognostic information in their letters could improve communication between oncologists, referring doctors and patients.